ANALISIS DAMPAK IKLAN NETFLIX TERHADAP KETERTARIKAN PENGGUNA INSTAGRAM - Rahmadani, Nabila Pramadita; Supiarza, Hery; Nafsika, Salsa Solli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Social media is a platform that is able to connect its users with other users online. One of the most widely used social media is Instagram. Instagram is a social media platform capable of displaying videos and photos that aim to inform and attract the attention of Instagram users in giving judgments. Instagram has ads that display various platforms that collaborate with Instagram. One platform that collaborates with Instagram is Netflix. Netflix is a streaming service platform that contains movies, television shows and series that have a marketing strategy to attract the attention of various platform users, companies and others. Netflix is working with Instagram to be able to attract the attention of Instagram users so they have the desire to use the streaming service provided by Netflix. However, every ad that has high quality and value, such as Netflix, does not necessarily have an impact on Instagram users. Therefore, this study aims to examine the impact of Netflix ads on Instagram users. This type of research is a quantitative research, namely by using a survey of Indonesian Education University students. This study found that Neflix has an influence on Instagram users with indicators from the results of the Neflix ad survey providing an attraction to subscribe. The implications of this research can be a reference for further research and a theoretical reference about the impact of Netflix ads on Instagram users.